THE FACULTY RESIDENCY PROGRAM. - Kaulback, Frank S. (The Accounting Review, 1954)
Abstract This article focuses on the faculty residency program in the in the U.S. as of January 1954. For several years in the U.S. programs of student internships have been available at certain institutions and through certain firms for the benefit of both students and employers. While the details of programs have varied, the essential features are somewhat similar. Because of the success of the student internship program it was doubtless inevitable that a similar program for accounting faculty members should be proposed. The purpose of the program would be to provide those without practical experience an opportunity to become familiar with the details of actual accounting practice, and to offer an opportunity to those with accounting experience either to broaden theft experience or to refresh it. The reaction to the proposed faculty residency program has been sufficiently favorable to encourage the American Accounting Association to participate in the actual arrangements for contacts between interested faculty members and participating firms and companies.